Factors affecting plant biodiversity in the homesteads of rural areas under process of modernization in Bangladesh (International Journal of Agricultural Research, Innovation and Technology, 2018)
A study was carried out at selected villages in Gazipur district of Bangladesh during 2008- 2009 to assess the changes in biodiversity of rural homesteads with modernization and factors affecting the biodiversity. Three villages were selected purposively considering their degree of modernization e.g. traditional, semi-modern and modern village and biodiversity at 40 randomly selected homesteads from each of the three villages were studied. Shannon- Wiener diversity index (H) value for traditional village (1.652) was statistically similar to semi-modern village (1.373) but significantly higher (t = 2.47*) than that of modern village (1.029). It indicates that plant biodiversity is decreasing significantly with modernization and/or urbanization. For assessing factors affecting biodiversity in the homesteads, a total of 26 factors were considered of them 15 factors had significant relationship with biodiversity. Factors like, family size, establishment of homestead, agricultural knowledge, nutritional knowledge, primary health care knowledge, environmental awareness, innovativeness, homestead area, income from homestead, savings, access to credit, disturbance of theft and predators, and utilization of modern agro-technologies had significant positive relationship; while ‘fragmentation of homestead’ and ‘sanitation’ had significantly negative relationship with homestead biodiversity. Linear multiple regression analysis showed that eight factors such as, agricultural knowledge, nutritional knowledge, environmental awareness, homestead area, income from homestead, innovativeness, homestead fragmentation and sanitation had significant contribution to homestead biodiversity. These eight significant factors explained 75.2 percent (adjusted R2 = 0.752) of the total variation in the homestead biodiversity. However, stepwise regression analysis revealed that ‘homestead area’ had the largest possible contribution (55.7%) to variation in the homestead biodiversity, followed in descending order by agricultural knowledge (9.5%), income from homestead (5.0%), environmental awareness (2.9%), sanitation (2.3%), nutritional knowledge (1.6%), innovativeness (1.0%) and fragmentation of the homestead (1.0%).Int. J. Agril. Res. Innov. & Tech. 8 (1): 44-54, June, 2018